Opsin 5 mediates violet light-accelerated wound healing in mammalian corneas - Nicolás M. Díaz; Xizhang Sun; Russell N. Van Gelder; Richard A. Lang; Ethan D. Buhr (Cell Reports, 2025)
Summary: The cornea is the transparent tissue at the ocular surface that generates most of the refractive power of the eye. Due to its exposed location, the cornea is uniquely in danger of injury. Rapid and efficient healing is required for high-acuity vision. Here, we show that epithelial corneal wounding induces Opn5, an opsin G-protein-coupled receptor (GPCR) sensitive to ultraviolet/violet light, at the cornea’s surface in both mice and primates. The expression of corneal Opn5 is coincident with the direct light sensitivity of multiple pathways, including circadian rhythms, damage-response genes, and immune modulators. The presence of a violet-light:dark cycle substantially accelerates epithelial wound closure both in vivo and ex vivo. Corneas lacking Opn5 have markedly impaired wound healing. Violet light also accelerates wound healing in non-human primate corneas and induces gene expression similar to mice. These results demonstrate that corneal wounding induces direct photosensitivity via Opn5, which accelerates wound healing in the cornea.